The Influence of Auditor Independence and Framing on Audit Judgment - Mulyandani, Vina Citra; Bella, Dinda (PT Larva Wijaya Penerbit, 2024)
This research aims to examine the influence of auditor independence and framing on audit judgment. The auditor independence variable is examined because in determining the audit opinion or audit judgment, the auditor needs to have strong independence. The framing variable is the auditor's way of conveying information regarding the opinion given. These two independent variables will be measured by how much they can influence the auditor in providing an audit opinion or audit judgment. This research uses a questionnaire distributed to 10 Public Accounting Firms in Bandung City registered with the Financial Services Authority. Nonpurposive sampling with convenience sampling was used. Data analysis was conducted using SmartPLS software version 4.0 through the outer model and inner model. The hypothesis results show that auditor independence has a significant positif effect on audit judgment, framing affects audit judgment, and auditor independence and framing simultaneously affect audit judgment.